DETERMINASI RASIO KEUANGAN TERHADAP RETURN SAHAM - Syaiful, Dian Yunita (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2016)
Return or the return on investment is a prime destination for investors in investing at a company. Stock investment will provide a benefit or return by the way, is the first to sell the stock until the price is strong, often referred to as capital gains or waiting dividend, which is part of the company profits are distributed to shareholders. The company's financial statements can be used as a basis for investors to take a decision to invest in shares in a particular company by taking into account financial ratios of the company. This study aims to determine the effect and significance of the test ratio Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), and Price Earning Ratio (PER) to return stock in LQ-45. period in this study is from the year 2009 until 2013. model of analysis used is multiple linear regression. The results showed partially significant effect on stock returns is the Current Ratio (CR), Return on Equity (ROE), and Price Earning Ratio (PER) where ROE is the dominant variable significant positive effect on stock returns. Simultaneously Current Ratio (CR), Debt to Equity Ratio (DER), Return on Equity (ROE), and Price Earning Ratio (PER) has an effect on stock returns by 59%, while 41% are influenced by other factors not examined in the study this.